An Evaluation of A Teaching File To Teach Novel - Lo, On Lee @ Anni (Universiti Malaysia Sarawak, (UNIMAS), 2006)
This study aims to evaluate the activities found in the selected Teaching File (Robinson Crusoe) and that is to find out the quality and the suitability of the activities for the teaching of literature. The data were collected by using checklists. The checklists are drawn from Rosli (1995) on the advantages of the teaching file, Garinger (2002) on Textbook selection for the ESL classroom and Cunningsworth (1994) on Evaluation and selecting EFL teaching materials. The findings are presented descriptively based on the criteria formulated on the checklists to evaluate the teaching file. It is hoped that by assessing the Teaching file (Robinson Crusoe), it will provide insights for the teachers to use the teaching file as a teaching aid during the teaching and learning of the literature subject and able to cater to the proficiency level of the students